2016
DOI: 10.18632/oncotarget.9617
|View full text |Cite
|
Sign up to set email alerts
|

Integrin alphavbeta3 enhances β-catenin signaling in acute myeloid leukemia harboring Fms-like tyrosine kinase-3 internal tandem duplication mutations: implications for microenvironment influence on sorafenib sensitivity

Abstract: Binding of leukemia cells to the bone marrow extracellular matrix (ECM) through integrins might influence drug response and the survival of acute myeloid leukemia (AML). However, the functions of integrin in AML are needed to be clarified. Data from The Cancer Genome Atlas (TCGA) were retrieved and integrin β3 (ITGB3) expression and prognostic significance for AML were analyzed. Integrin alphavbeta3 (αvβ3) in sorafenib sensitivity and signaling pathway of FLT3-ITD AML cells was evaluated in vitro. The level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
0
50
0
1
Order By: Relevance
“…Moreover, different in vivo studies have identified β3 integrin as an integral part of leukemogenesis in AML, although it is dispensable for normal hematopoiesis (Miller et al, 2013). Integrin β3 was recently shown to enhance Wnt signaling in AML cells by mediating resistance to the kinase inhibitor sorafenib (Yi et al, 2016). In addition, the integrin-binding glycoprotein CD98 was shown to promote AML proliferation and maintenance of leukemic stem cells through an increased engagement with the BMM, while anti-CD98 blockade inhibited AML growth (Bajaj et al, 2016).…”
Section: Cell Adhesion Molecules and Other Niche Components Involved mentioning
confidence: 99%
“…Moreover, different in vivo studies have identified β3 integrin as an integral part of leukemogenesis in AML, although it is dispensable for normal hematopoiesis (Miller et al, 2013). Integrin β3 was recently shown to enhance Wnt signaling in AML cells by mediating resistance to the kinase inhibitor sorafenib (Yi et al, 2016). In addition, the integrin-binding glycoprotein CD98 was shown to promote AML proliferation and maintenance of leukemic stem cells through an increased engagement with the BMM, while anti-CD98 blockade inhibited AML growth (Bajaj et al, 2016).…”
Section: Cell Adhesion Molecules and Other Niche Components Involved mentioning
confidence: 99%
“…30 Active b-catenin was up-regulated in stroma-adherent cells, suggesting a role in AML-stromal interaction through direct binding, and of note integrin avb3 has been implicated in modulating sensitivity to sorafenib. 31 This observation was absent in adhesion to NBM-derived MSCs, suggesting a therapeutic window for the malignant versus healthy BM niche.…”
Section: Discussionmentioning
confidence: 96%
“…Its knockdown results in impairment of LSC homing (specifically to the bone marrow endosteal surface), downregulation of an LSC transcriptional programme, and induced differentiation [17]. ITGB3 is upregulated in the CD34 + CD38blast subset [35] and has been implicated in chemoresistance [36]. Osteopontin can augment ITGB3-mediated spreading and signal transduction [20].…”
Section: Discussionmentioning
confidence: 99%